T Cell factor 1 represses CD8+ effector T cell formation and function - Tiemessen, Machteld M; Baert, Miranda R M; Kok, Lianne; van Eggermond, Marja C J A; van den Elsen, Peter J; Arens, Ramon; Staal, Frank J T (The Journal of immunology (1950), 2014)
The Wnt-responsive transcription factor T cell factor 1 (Tcf1) is well known for its role in thymic T cell development and the formation of memory CD8(+) T cells. However, its role in the initial phases of CD8(+) T effector cell formation has remained unexplored. We report that high levels of Wnt signaling and Tcf1 are operational in naive and memory CD8(+) T cells, whereas Wnt signaling and Tcf1 were low in effector CD8(+) T cells. CD8(+) T cells deficient in Tcf1 produce IFN-γ more rapidly, coinciding with increased demethylation of the IFN-γ enhancer and higher expression of the transcription factors Tbet and Blimp1. Moreover, virus-specific Tcf1(-/-) CD8(+) T cells show accelerated expansion in acute infection, which is associated with increased IFN-γ and TNF production and lower viral load. Genetic complementation experiments with various Tcf1 isoforms indicate that Tcf1 dosage and protein stability are critical in suppressing IFN-γ production. Isoforms lacking the β-catenin binding domain are equally effective in inhibiting CD8(+) effector T cell formation. Thus, Tcf1 functions as a repressor of CD8(+) effector T cell formation in a β-catenin/Wnt-independent manner.